Living the Climate Change: Perception of women users of the Family Health Unit in Recife-PE (Research, Society and Development, 2021)
Female aging represents a challenge to prioritize prevention and health promotion measures, and attention to menopause and climate change stands out. This study aimed to understand and analyze the level of information of women in the climacteric phase, attended at a family health unit (USF) in Recife - PE. Data were obtained through a structured interview applied after the consultation, following all research ethics guidelines. The answers of the 20 volunteers, from 45 to 79 years old, showed the profile of these women, the most frequent symptoms and problems and the main changes identified in this phase. Most women reported experiencing hot flashes and psychological symptoms such as malaise and irritation. In addition to relating the climacteric phase to negative feelings. The users' misinformation and the need for better support and guidance from health professionals were evident. Still, it was clear the importance of valuing the family over adaptation, what should be considered by the multidisciplinary team. Experiences reported were diversified, reaffirming that each woman lives this phase individually, as well as the adequacy of her reception should be, in an individualized, integrated and respectful way.